Spiral-Phased Laguerre-Gaussian Modes Generation in SWDM over Few Mode Fiber based on Electrical Equalization. (April 2020) - Ghazi, Alaan; Fareed, Alaa; Masunda, Tendai; Aljunid, S. A.; Idrus, Syed Zulkarnain Syed; Amphawan, Angela; Al-dawoodi, Aras; Rashidi, C. B. M; Fadhel, Ibrahim Eskandar Ibrahim
Abstract: Space division multiplexing, in conjunction with wavelength division multiplexing, is a powerful mechanism that increases spatial channels significantly in a single optical fiber. Spiral Phased-Laguerre-Gaussian (SP-LG) modes indicate that they effectively reduce mode coupling, thereby increasing the channel response and performance positively. However, mode-coupling influence optical fiber system leads to inter-symbol interference (ISI) between the channels and reduces both capacity and distance. In this paper, we apply the SP-LG modes in a space wavelength division multiplexing over a few-mode fiber system. The results demonstrate significant improvements in reducing channels effects and ISI. The performance evaluations are based on the bit-error-rate (BER), eye diagram and spectrum analyzer.